A New Method for Stimulating the Fertilizing Capability of Sperm Cells - Lubart, Rachel (Recent Patents on Biomedical Engineering (Discontinued), 2009)
The effects of visible light irradiation on various aspects of cell metabolism have been recognized in recent years, and extensive literature exists on the application of laser phototherapy in various biological systems. The biostimulative effect of light in the visible range has been attributed to minute amounts of light-induced reactive oxygen species (ROS) formation. In sperm cells, low amounts of ROS were found to enhance acrosome reaction and in vitro fertilization. These findings led us to patent a method for stimulating the fertilizing capability of sperm cells using light irradiation. In the present paper, US Patent No. 6379939 is discussed and results demonstrating light induced ROS in sperm cells are summarized.
Keywords: sperm